Are Child Cognitive Characteristics Strong Predictors of Responses to Intervention? A Meta-Analysis. (September 2015) - Stuebing, Karla K.; Barth, Amy E.; Trahan, Lisa H.; Reddy, Radhika R.; Miciak, Jeremy; Fletcher, Jack M.
We conducted a meta-analysis of 28 studies comprising 39 samples to ask the question, "What is the magnitude of the association between various baseline child cognitive characteristics and response to reading intervention?" Studies were located via literature searches, contact with researchers in the field, and review of references from the National Reading Panel Report. Eligible participant populations included at-risk elementary school children enrolled in the third grade or below. Effects were analyzed using a shifting unit of analysis approach within three statistical models: cognitive characteristics predicting growth curve slope (Model 1, mean r = .31), gain (Model 2, mean r = .21), or postintervention reading controlling for preintervention reading (Model 3, mean r = .15). Effects were homogeneous within each model when effects were aggregated within study. The small size of the effects calls into question the practical significance and utility of using cognitive characteristics for prediction of response when baseline reading is available.